Design, Manufacture, and Testing of An Affordable External Bone Fixator Taylor Spatial Frame - Achmad Fauzy, Nandy
Broken bones are injuries that often occur. Fracture is often caused by traffic accident. For some cases, compound fractures are quite complex requiring taylor spatial frame as bone fixation tool. Taylor spatial frame has 6 degrees of freedom. However, taylor spatial frame is hard to obtain in Indonesia and cost ineffective. Therefore, it is required to develop low cost taylor spatial frame. In design process, several design criteria were reviewed and then one design concept was chosen. Taylor spatial frame consists of two rings and six struts. Static analysis using numerical method on ANSYS was used to ensure whether the design is strong enough to withstand applied load. Based on static analysis, the design continuously iterated to get the optimum design. Machining processes are used to manufacture taylor spatial frame from raw materials. Some components directly use common component from the market and some going through a little modification beforehand. Taylor spatial frame is made of AA7075 T6 and SS304. Lastly, kinematic tests were performed to test whether taylor spatial frame could work properly. Nylon rod was used to model broken bones and mounted on taylor spatial frame on deformed condition. Bone deformation parameters were measured using marker tracking form the anteroposterior, lateral, and axial view. The parameters are then used as software input, and the output were length of each strut. The length of the struts was set to follow the data from the software and then nylon was measured to show how big the error was. Taylor spatial frame was successfully made at a cost of 2,778,800.00 IDR with 1 – 3 mm error.